Postural changes and pain in the academic performance of elementary school students - Maria Homéria Leite de Morais Sampaio; Lucia Conde de Oliveira; Francisco José Maia Pinto; Maria Zuleide Amorim Muniz; Regina Cláudia Tabosa Ferreira Gomes; Geni Rodrigues Loiola Coelho
Abstract Postural changes and pain in the spine of children and adolescents of school age are influenced by the permanent incorrect sitting position, misuse of furniture and weight of the backpack. The aim of this study was to verify postural changes and pain in the academic performance of elementary school students. It was a cross-sectional study, with a descriptive and analytical approach. The subjects were 83 elementary students, aged 8 to 12 years, of Kindergarten and Elementary Education at Paulo Sarasate Municipal School, Ceará. It was performed from March to June 2008. In the physical examination it was used an evaluation form, based on Global Postural reeducation, by Souchard method, which included the variables: compromised anterior, posterior, superior shoulder muscle chains and pain and, in academic performance, a semi-structured questionnaire with the variables: behavior, attendance and performance. The data was stored in the Statistical Package for the Social Science (SPSS) version 18.0. In the descriptive analysis, absolute and relative frequencies were used, and in the inferential analysis, the following tests were applied: Mann-Whitney, to verify the existence of significant differences in changes in groups A and B, at a significance level of 5%, and the F statistical test, for comparing postural changes and pain, in the three grades. Results: it was noted that the majority of the students presented postural changes, such as forward head, lifted shoulders, dorsal hyperkyphosis and pain, which predominantly occurred in the anterior chain, when compared with the posterior and superior chains. These changes in both groups were statistically significant only in subjects of the fifth grade with satisfactory academic performance and behavior. It was concluded that there was no association between postural changes and school performance, although it was influenced by pain.